Ethnoscience-Based Science Learning in Sasak Ethnic Culture: Literature Review - M. Harja Efendi; Agus Muliadi (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to elaborate on science learning based on indigenous science, the culture of the Sasak ethnics of Lombok. This study is library research with data sources from previous research articles that have topics related to science learning, science concepts, ethnoscience, and songket cloth, poteng jaje tujak, and bale adat. The procedure in literature study research is carried out in stages, namely collecting library data, reading, taking notes, studying, collecting concepts or manuscripts, then carrying out elaboration and explanation of the collected data/text. The study results show that (1) the nature of learning science can be classified into three dimensions, namely science as a product, science as a process, and science as an attitude; (2) indigenous science in songket wayang motifs, subahnale motifs keker motifs four star, and alang/lumbung which have relevance to the basic science competence of â€œanalyzing the reproductive system in plants and animals and the application of technology to the reproductive system of plants and animalâ€; (3) indigenous science in the materials for making bale adat has relevance to the basic competence of natural science on â€œanalyzing the interrelationships of plant tissue structures and their functions, as well as technology inspired by plant structuresâ€; (4) indigenous science in the process of making poteng jaje tujak has relevance to the basic competence of natural science regarding â€œapplying the concept of biotechnology and its role in human lifeâ€.